Compression of Astronomical Image Using Five Modulus Method - Khanjer , Ebtesam F.; Shnain, Saif Kamil; Abbas, Ban Abed Al-Razaq (Iraqi Journal of Science, 2022)
The computer vision branch of the artificial intelligence field is concerned withdeveloping algorithms for analyzing image content. Data may be compressed byreducing the redundancy in the original data, but this makes the data have moreerrors. In this paper image compression based on a new method that has beencreated for image compression which is called Five Modulus Method (FMM). Thenew method consists of converting each pixel value in an (4x4, 8×8,16x16) blockinto a multiple of 5 for each of the R, G and B arrays. After that, the new valuescould be divided by 5 to get new values which are 6-bit length for each pixel and itis less in storage space than the original value which is 8-bits.